Pharmacokinetics and Cardiovascular Effect of Etoricoxib in the Absence or Presence of St. John’s Wort in Rats - Radwan, M. A.; Baky, N.A. A.; Zaghloul, I.; Aboul-Enein, H. Y. (Arzneimittelforschung, 2012)
The effect of chronic administration of etoricoxib (EXB), in the absence or presence of St. John’s Wort (SJW), on its pharmacokinetic parameters and blood pressure was investigated in rats.Rats were divided into 3 groups, each group received daily different oral treatment for 3 weeks. Rats’ blood pressures were monitored initially, after 1 and 3 weeks of treatment, and after 1 week of discontinuing dosing of both drugs. EXB pharmacokinetic parameters in the absence or presence of SJW were calculated after 3 weeks.SJW was significantly affected EXB pharmacokinetic parameters. The steady state peak plasma concentration and terminal half-life were reduced by 32% and 91%, respectively, due to a > 3 fold increase in its apparent clearance which is a concentration and time dependent effect. EXB was significantly increased (P<0.001) Rats’ blood pressure while, co-administration of EXB and SJW was not significantly affect (P>0.05) rats’ blood pressure as compared to the control.Monitoring blood pressure of patients anticipated taking EXB for extended period should be advised. The co-administration of SJW with EXB should be avoided since SJW would greatly reduce EXB concentrations by inducing its metabolism.
Keywords: etoricoxib; St. John’s Wort; pharmacokinetics; blood pressure; rats